Enhancing English Productive Skills Learning through Technology-Mediated Instructions: Meeting Students’ Expectations and Needs - Nur Lailatul Aqromi; Adi Surya Irawan (Journal of English for Academic and Specific Purposes)
This study examines the qualitative enhancement of students’ English productive skills, explicitly speaking and writing, following an eight-session Basic English course employing technology-facilitated teaching. At the outset, students completed a questionnaire to express their expectations, particularly concerning improving their English productive skills. Throughout the course, students participated in eight sessions that integrated technology-enhanced learning tools, such as Quizizz, video presentations, and augmented PowerPoint slides. Additionally, students were encouraged to explore and present their ideas using various technological platforms. Following the completion of the sessions, a final questionnaire and interviews were carried out to assess the effectiveness of the instruction. The findings demonstrated substantial enhancements in students' written and spoken proficiency, encompassing heightened speaking confidence, broadened vocabulary, and improved writing ability. The findings suggest that integrating technology in instructional approaches significantly enhances students' learning experiences and successfully fulfills their initial expectations.